Faktor-Faktor Yang Mempengaruhi Organizational Citizenship Behavior (Studi Pada Pegawai KPP Madya Semarang) - Purwandi Purwandi; Tristiana Rijanti (Jurnal Dinamika Ekonomi & Bisnis, 2022)
The purpose of this study is to analyze the influence of servant leadership and career development on Organizational Citizenship Behavior (OCB) of KPP Madya Semarang employees. It analyzes the influence of servant leadership, career development and OCB on employee performance of KPP Madya Semarang and analyzes OCB which mediates the effect of servant leadership and career development on employee performance of KPP Madya Semarang. The population in this study were all employees in the KPP Madya Semarang consisted of 108 people. The sample were 108 employees of KPP Madya Semarang obtained from census sampling technique. The data collection method used a questionnaire. The data were analyzed using linear regression analysis. The results showed that servant leadership had a significant positive effect on Organizational Citizenship Behavior (OCB). Career development had a significant positive effect on Organizational Citizenship Behavior (OCB). Servant leadership had a positive and significant effect on employee performance. Career development had a significant positive effect on employee performance. OCB had a significant positive effect on employee performance. OCB mediated the effect of servant leadership on employee performance. OCB mediated the effect of career development on employee performance.